Utilization pattern of social welfare schemes among women beedi workers in comparison with non-beedi workers - Mangasuli, Vijayalaxmi; Sherkhane, Mayur S. (International Journal Of Community Medicine And Public Health, 2016)
Background: Social security is basic fundamental human right, felt need and demand of the people for their wellbeing in the society, its fulfillment will contribute in achieving various developmental goals of the nation. In India, beedi industry has one of the largest employers of workers, after agriculture and construction, of which most of them are from socioeconomically backward populations living in urban slums and these people are the one who utilize social welfare and healthcare schemes to the highest level. Thus this study was done to know socio-demographic profile and utilization pattern of social welfare schemes among women working as beedi workers in comparison with non-beedi workers. Methods: Community based cross sectional study among 100 beedi workers and 100 non-beedi workers residing in urban slums, for a period of three months. House to house survey was done and utilization pattern of social welfare schemes were noted. Results: Of the 200 women, maximum 34% beedi workers and 30% non-beedi workers were in the age group of 30-39 years, 90% beedi workers and 66% non-beedi workers were illiterates and 62% beedi worker as well as 82% non-beedi worker belonged to nuclear family. 54% and 42% were from class IV socioeconomic status. 96% of beedi workers were utilizing BPL services compared to 84% of non-beedi workers (χ2=5.355, df=3, p=0.005). In addition, 78% beedi workers were utilizing health and education benefit from beedi worker welfare fund scheme. 68% of the beedi workers were utilizing BPL services, inspite their monthly income was more than 1000Rs compared to 54% non-beedi workers whose monthly income was less than 1000Rs, which was found to be statistically significant (χ2=22.33, df=1, p<0.0001). It was found that years of employment and working hours also had significant impact in utilizing these services. Conclusions: Better utilization of social welfare services was seen among beedi workers because of the awareness present in their working environment compared to non-beedi workers. There is need to emphasize women living in urban slums to utilize social services to the maximum extent for their welfare and better life.